Specific Aggregation of SV40-Transformed Cells by Ornithine, Leucine Copolymers - Duksin, Dan (1970)
A basic copolymer of ornithine and leucine (1:1) was shown to rapidly agglutinate, in the absence of serum, normal cells and cells transformed by viral and nonviral carcinogens. This agglutination was inhibited by addition of serum. In presence of serum, the same copolymer and those of ornithine and valine (1:1) and arginine and leucine (1:1), produced a specific aggregation of simian virus 40 (SV40)-transformed cells cultured for about 24 hr after addition of the peptide. The rapid agglutination and SV40-specific aggregation could not be inhibited by a variety of individual amino acids or carbohydrates. The specific aggregation could be detected in mixtures of SV40-transformed and other cells, and it was not prevented by x-irradiating the cells with 4000 R. Aggregation of the SV40-transformed cells was inhibited by acidic polyamino acids provided these were added not later than about 5 hr after addition of the basic copolymer. The results indicate that the basic copolymer, in the presence of serum, produces a change in SV40-transformed cells, presumably in the surface membrane, that causes the cells to aggregate. In addition to the aggregation of cells transformed by SV40, cells transformed by adenovirus 12, which did not contain detectable SV40-specific nuclear tumor (T) antigen, were also aggregated by the basic copolymer in the presence of serum. This indicates that the ornithine, leucine copolymer is able to detect an SV40-like change in the surface membrane of cells transformed by adenovirus 12.